CARACTERÍSTICAS DEMOGRÁFICAS, HÁBITOS DE VIDA E HISTORIA DEL CONSUMO DE TABACO DE LOS FUMADORES OCASIONALES EN ESPAÑA - Lucía Díez Gañán; Fernando Rodríguez Artalejo; José Ramón Banegas Banegas; Pilar Guallar Castillón; Luis Fernández Pacheco; Juan del Rey Calero (Revista Española de Salud Pública, 2002)
Back ground. This study des cribes the so cio de mo grap hic cha rac te ris tics, health-re lated li fest yle, and his tory of to bac co con sump tion of the oc casional smo kers in Spain, and exa mines whet her they show dif fe ren ces against daily smo kers. Met hods. Data were ob tai ned from the Na tional Health Sur vey of Spain, ca rried out in 1993 through hou sehold in ter - views on a sam ple re pre sen ta ti ve of the non-ins ti tu tio na li sed po pu la tion aged 16 year and ol der. Analy ses were per for med with lo gis tic re gres sion and ad justed for so cio de mo grap hic, health-sta te and life-style va ria bles. Results. Out of the 6,668 smo kers in the sur vey, oc casional smokers were 9.2%, whi le daily smo kers of £5 ci garettes and >5 cigarettes were 9.9% and 80.9%, res pectively. As com pared with daily smo kers of >5 ci garettes, oc casional smo kers were more fre - quently wo men (odds ra tio (0R):2.12; CI95%:1.72-2.61), youn ger (OR aged 25-44 ver sus 16-24 years: 0.75; 0.58-0.96), with lo wer alcohol con sumption (p for li near trend: 0.0349), and hig her lei su - re-time physi cal ac tivity (p for li near trend: <0.0001). On the day they smo ke, oc casional smo kers used to con sume less ci garettes than daily smo kers (p<0.0001). Occa sional smo kers were more frequent among young smo kers (aged less than 20) with re latively short his tory of to bacco con sumption (less than 20 years), and also among ol der smo kers (aged 65 year and ol der) with lon ger his tory of con sumption (over 50 years). Daily smo kers of £5 ci garettes showed cha racteristics mid way bet ween tho se of oc casional and daily smo kers of >5 ci garettes. Con clu sions: Occa sio nal smo kers show so cio de mo grap hic cha rac te ris tics, health-re lated li fest yle, and his tory of to bac co con sump tion dif fe rent from daily smo kers. Such dif fe ren ces sug gest that re search and in ter ven tion pro grams spe cifically tai lo red to oc ca sio nal smo kers should be de veloped.